2023
DOI: 10.1186/s13098-023-01003-2
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of diabetic retinopathy in Brazil: a systematic review with meta-analysis

Abstract: Aims To evaluate the prevalence of diabetic retinopathy (DR) in Brazilian adults with diabetes mellitus via a systematic review with meta-analysis. Methods A systematic review using PubMed, EMBASE, and Lilacs was conducted, searching for studies published up to February 2022. Random effect meta-analysis was performed to estimate the DR prevalence. Results We included 72 studies (n = 29,527 individuals)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 99 publications
0
0
0
Order By: Relevance
“…The prevalence of DR in Pakistan was reported to be 28%, with 9% of patients having eye disease severe enough to threaten their sight. The prevalence of DR in Pakistan was reported to be 28%, with 9% of patients having eye disease severe enough to threaten their sight [ 21 , 38 ]. The same study also reported that the prevalence of DR ranges from 10.6% to 91.34% [ 38 ], and that sight-threatening diseases very between 4% and 46% [ 20 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The prevalence of DR in Pakistan was reported to be 28%, with 9% of patients having eye disease severe enough to threaten their sight. The prevalence of DR in Pakistan was reported to be 28%, with 9% of patients having eye disease severe enough to threaten their sight [ 21 , 38 ]. The same study also reported that the prevalence of DR ranges from 10.6% to 91.34% [ 38 ], and that sight-threatening diseases very between 4% and 46% [ 20 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of DR in Pakistan was reported to be 28%, with 9% of patients having eye disease severe enough to threaten their sight [ 21 , 38 ]. The same study also reported that the prevalence of DR ranges from 10.6% to 91.34% [ 38 ], and that sight-threatening diseases very between 4% and 46% [ 20 , 23 ]. The prevalence of DR in diabetic worldwide is 27.0% [ 39 ], but region-specific studies indicate a prevalence of 31.6% in Africa and 19.48% in Ethiopia [ 40 ] (Table 1 ).…”
Section: Introductionmentioning
confidence: 99%
“…Al igual que diferentes complicaciones, entre ellas la retinopatía diabética, que es la más común de las complicaciones en pacientes con DM. Con tasas notoriamente altas, como en el caso de Brasil por ejemplo, en dónde se estima entre el 7 al 44% de todos los pacientes con DM (Chagas et al, 2023).…”
Section: Introductionunclassified